The Influence of Lifestyle and Financial Literacy on the Financial Behavior (A Case Study on Management Students at University of Tribhuwana Tunggadewi) - Maria Defira Sari; Elly Lestari; Moch Nurhidayat (International Research & Development for Human Beings (IRDH), 2025)
Lifestyle and financial literacy are crucial factors influencing individual financial decision-making. A solid understanding of financial concepts and personal financial management is essential for effective financial behavior. This research aims to examine the influence of lifestyle and financial literacy on the financial behavior of Management students from the 2021-2022 cohort, both partially and simultaneously. The study adopts a quantitative approach with data collected through questionnaires and surveys. The analysis reveals that both lifestyle and financial literacy contribute to shaping students’ financial behavior. The findings highlight the importance of fostering financial awareness and promoting responsible lifestyle choices among students. This study contributes to the growing body of knowledge in financial behavior research, particularly in the context of higher education, and offers practical insights for improving students' financial management skills.